SINTESIS TiO2 TERDOPING Bi3+ DAN UJI AKTIVITAS FOTOKATALISIS ANTIBAKTERI E.coli DENGAN BANTUAN SINAR TAMPAK (SYNTHESIS OF Bi3+ DOPED TiO2 AND PHOTOCATALYSIS ACTIVITY TEST OF E.coli ANTIBACTERIA UNDER VISIBLE IRRADIATION) - Annisa Furqonita; Anthoni B. Aritonang; M. Agus Wibowo (Tanjungpura University, 2021)
The synthesis of Bi3+ doped TiO2 was carried out using the sol-gel method with the precursor solution of titanium tetraisopropoxide (TTiP). Bi3+ cation dopant is done to reduce the energy of the TiO2 band gap so that it can be active in the visible light region. The synthesized Bi(III) –TiO2 photocatalyst was characterized using DRS UV-Vis, FTIR, and EDX. The results of the DRS UV-Vis analysis showed that 1% Bi(III) –TiO2 photocatalyst had a bandgap energy of 2.79 eV or equivalent to a wavelength of 469.97 nm. Infrared spectra show that there is a unique absorption at the wave number 956,56 cm-1 which is the absorption of the vibration Bi-O-Ti group. Photocatalyst Bi(III) -TiO2 was then tested for antibacterial activity against E. coli in polluted water. The activity test was carried out using the turbidimetric method by UV-vis spectrophotometry. The results of the activity test for 120 minutes with the help of visible light showed that the photocatalyst Bi(III) –TiO21% had the best antibacterial activity. The decrease in the number of E. coli in the water reached 48.54%.